A Model to Assess Technological Innovations at Institutions of Higher Learning in Kenya - Muchiri, Rajab Philip (TexilaJournal, 2017)
Objective: The aim was to develop an innovation assessment model to analyse the impact of broadband in spurring innovations in Kenya by studying the role of broadband diffusion, the impact of broadband collaborations, the influence of electronic research and the role of online broadband products usability. Background: Many countries in Africa invest in broadband infrastructure because they have realized that broadband encourages innovation leading to economic development and prosperity. Understanding the relationship between universities, business enterprises and government enabled by broadband is critical in assessing a country's innovative capacity. Methodology: This study applied descriptive survey research design. It used a logistic regression model as an inferential analysis tool in the quantitative aspects of the research. The target population for this study was institutions of higher learning (IHL) operating in Kenya by 31st December, 2015 which included both private and public accredited universities in Kenya. Results: The response rate from the sampled population was at 75% Reliability measures were above the recommended level of 0.70 as an indicator for adequate internal consistency. The overall model evaluation, goodness-of-fit statistics, statistical tests of individual predictors and validations of predicted probabilities. Showed that the data fitted the model and the model performed well. Conclusion: Institutions of higher learning in Kenya have a positive but low capacity in technological innovation implementation. Broadband diffusion is inhibited by poor infrastructural development attributed to high costs of connections and bandwidth acquisition and a high demand for broadband among the students and staff.
Keywords: Broadband; Innovation; Internet; Education; Model